Asymmetric Allylation by Chiral Organocatalyst‐Promoted Formal Hetero‐Ene Reactions of Alkylgold Intermediates. (20th November 2020) - Dong, Guizhi; Bao, Ming; Xie, Xiongda; Jia, Shikun; Hu, Wenhao; Xu, Xinfang
Abstract: An unprecedented catalytic asymmetric allylation of isatins and isatin‐derived ketimines is reported enabled by a gold and chiral organocatalyst cooperative catalysis strategy. This method offers expeditious access to chiral 2, 5‐disubsituted alkylideneoxazolines containing vicinal stereogenic centers, mainly in optically pure form, and which are otherwise impossible to access. Mechanistic evidence reveals the presence of an alkylgold intermediate, and an X‐ray crystal structure of the allylgold species illuminates its unique stability and reactivity. An asymmetric formal hetero‐ene reaction of this gold intermediate, involving a dearomatization process, is enabled with assistance of a quinine‐derived squaramide catalyst. This novel discovery extends the synthetic applications of gold complexes and the versatility of gold catalysis. Abstract : An asymmetric allylation reaction of isatins/ketimines with N ‐propargylamide is reported that gives access to alkylideneoxazolines mainly in optically pure form. The key alkylgold intermediate, which possesses allylgold reactivity, has been confirmed by X‐ray crystallographic analysis. The asymmetric formal hetero‐ene reaction of this species, involving a dearomatization process is enabled with the assistance of a quinine‐derived squaramide catalyst.